2007
DOI: 10.1073/pnas.0611449104
|View full text |Cite
|
Sign up to set email alerts
|

The limited impact of kinship on cooperation in wild chimpanzees

Abstract: The complex cooperative behavior exhibited by wild chimpanzees generates considerable theoretical and empirical interest, yet we know very little about the mechanisms responsible for its evolution. Here, we investigate the influence of kinship on the cooperative behavior of male chimpanzees living in an unusually large community at Ngogo in Kibale National Park, Uganda. Using long-term field observations and molecular genetic techniques to identify kin relations between individuals, we show that male chimpanze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
306
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 356 publications
(323 citation statements)
references
References 43 publications
11
306
4
4
Order By: Relevance
“…As we will see below, coalitions can serve different functions (van Schaik et al, 2006); they can be observed among different sex and age classes (reviewed in Chapais, 1995); they can involve kin (e.g., Riss & Goodall, 1977;Chagnon & Bugos, 1979;Wahaj et al, 2004), non-kin (e.g., Vigilant et al, 2001;Langergraber et al, 2007;Schülke et al, 2010), and friends or acquaintances (Hruschka & Henrich, 2006;Hruschka, 2010). As this brief review makes clear, coalitionary patterns are varied, and understanding this diversity would be greatly enhanced by formal modelling that would allow us to identify the general conditions under which coalition formation is expected to evolve, characterize the degree of variability expected, and predict when coalitions should, and should not, occur.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…As we will see below, coalitions can serve different functions (van Schaik et al, 2006); they can be observed among different sex and age classes (reviewed in Chapais, 1995); they can involve kin (e.g., Riss & Goodall, 1977;Chagnon & Bugos, 1979;Wahaj et al, 2004), non-kin (e.g., Vigilant et al, 2001;Langergraber et al, 2007;Schülke et al, 2010), and friends or acquaintances (Hruschka & Henrich, 2006;Hruschka, 2010). As this brief review makes clear, coalitionary patterns are varied, and understanding this diversity would be greatly enhanced by formal modelling that would allow us to identify the general conditions under which coalition formation is expected to evolve, characterize the degree of variability expected, and predict when coalitions should, and should not, occur.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…A strong bias towards female philopatry (Smuts, 1987), however, limits the occurrence of male-male nepotistic coalitions in primates. As a result, increasing one's inclusive fitness is not expected to be a major benefit of coalitions among primate males (Chapais, 1995;van Schaik et al, 2006), with rare exceptions (Langergraber et al, 2007).…”
Section: Increasing Inclusive Fitness Benefitsmentioning
confidence: 99%
See 3 more Smart Citations